Oxygen uptake kinetics and performance in swimming - Reis, J. F.; Alves, F. B. (Biomechanics and Medicine in Swimming XI, 2010)
The purpose of this study was to describe VO2 kinetics throughout the heavy and severe domains during swimming. Nine swimmers completed two swimming tests to measure the conditioning indexes (ventilatory threshold (VT), respiratory compensation point (RCP), and VO2max) and VO2 kinetics (two trials intensities set at 2.5% below and above the crawl velocity at RCP, lasting 420s). In both cases, a portable breath-by-breath system connected to a respiratory snorkel and valve was used. The trial below RCP elicited only a sub-maximal rate (91.6±5.7%VO2max), with a slow component of 391ml/min beginning after 154s. The trial above RCP showed a time delay of 188s for the slow component (399ml·min-1), eliciting a rate of 104.6±9.5%VO2max. Thus, expected VO2 kinetics for heavy and severe domains was characterized around RCP. 1Paulista State University, Brazil 2Faculty of Human Kinetics, Technical University of Lisbon, Portugal The purpose of this study was to describe VO2 kinetics throughout the heavy and severe domains during swimming. Nine swimmers completed two swimming tests to measure the conditioning indexes (ventilatory threshold (VT), respiratory compensation point (RCP), and VO2max) and VO2 kinetics (two trials intensities set at 2.5% below and above the crawl velocity at RCP, lasting 420s). In both cases, a portable breath-by-breath system connected to a respiratory snorkel and valve was used. The trial below RCP elicited only a sub-maximal rate (91.6±5.7%VO2max), with a slow component of 391ml·min-1 beginning after 154s. The trial above RCP showed a time delay of 188s for the slow component (399ml/min), eliciting a rate of 104.6±9.5%VO2max. Thus, expected VO2 kinetics for heavy and severe domains was characterized around RCP.